Pengaruh Kepemimpinan Transformasional dan Motivasi Kerja Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening Di PT Haleyora Power Area Padang - Nadia Putri Yasma; Robby Dharma; Omia Crefioza (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of transformational leadership and work motivation on employee performance with job satisfaction as an intervening variable at PT. Haleyora Power Area Padang. This research employs a quantitative approach using a survey method. The population of this study consists of all employees of PT. Haleyora Power Area Padang, with a census sampling technique. Data were collected through questionnaires and analyzed using the Partial Least Squares (PLS) method. The results indicate that transformational leadership and work motivation have a positive and significant effect on employee performance. Furthermore, transformational leadership and work motivation also have a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on employee performance and is proven to mediate the effect of transformational leadership and work motivation on employee performance. These findings imply that improving employee performance can be achieved through effective transformational leadership, enhanced work motivation, and increased job satisfaction.